Sodium ion battery layered oxide positive electrode material and preparation method thereof

By preparing a sodium ion battery layered oxide positive electrode material, the combination of composite layered oxide and polycarbazole is used to solve the problem of phase change and cracks of the positive electrode material during the cycle, achieving higher cycle stability and battery performance.

CN119133421BActive Publication Date: 2025-03-11河南湛拓新能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411615763.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-11
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing sodium ion battery layered oxide positive electrode materials are prone to phase change and cracks during the cycle, resulting in a significant decline in battery performance.

Method used

Through the preparation method, the sodium salt, precursor and metal oxide are mixed evenly and then cut into pieces and calcined to form a composite layered oxide. The hyperbranched framework is formed by reaction of tripolymer cyanochloride and 2-bromo-4-trifluoromethylphenol. Then the carbazole ring is introduced by carbazole reaction, and finally the composite layered oxide is coated with polycarbazole to form a stable positive electrode material.

Benefits of technology

It improves the cycle stability of the positive electrode material, significantly improves the performance of the battery, extends the cycle stability life, and enhances the conductivity and high temperature stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of sodium ion battery positive electrode materials, and in particular to sodium ion battery layered oxide positive electrode materials and a preparation method thereof, and is used to solve the problem that the existing sodium ion battery layered oxide positive electrode materials are prone to phase change and cracks during a cycle, resulting in a significant decrease in battery performance. The sodium ion battery layered oxide positive electrode material is composed of a composite layered oxide and a polycarbazole protective layer, the composite layered oxide is composed of two or more metal ions, and has excellent electrochemical performance. After being wrapped with polycarbazole as a protective layer, it can not only effectively isolate the composite layered oxide from direct contact with an electrolyte, but also suppress the volume change caused by uneven embedding and extraction of sodium ions during charging and discharging. In addition, fluorine atoms in the polycarbazole protective layer can give it excellent high-temperature stability and chemical stability, so that the protection effect is better, and the cycle stability of the positive electrode material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sodium ion battery positive electrode materials, and in particular to sodium ion battery layered oxide positive electrode materials and a preparation method thereof. Background Art

[0002] Electrochemical energy storage, as a technology with high energy conversion efficiency, has attracted widespread attention. As the problems of lithium resource scarcity, uneven distribution, and difficulty in development and utilization have gradually been exposed, sodium-ion batteries, which have a wide distribution of resources, have regained attention, and finding low-cost alternatives has become the focus of attention. Sodium-ion batteries are considered to be a competitive alternative because of their similar performance to lithium-ion batteries and the abundant sodium resources in the earth's crust, which can greatly reduce costs.

[0003] Positive electrode materials are considered to be the key to developing high-performance sodium-ion batteries. Layered oxide positive electrode materials have attracted much attention due to their advantages such as high voltage and high capacity, but they are prone to phase change and cracking during the cycle, resulting in a significant decrease in battery performance. Therefore, the development of a sodium-ion battery layered oxide positive electrode material and its preparation method is of great significance to improve the cycle stability of layered oxide positive electrode materials. Summary of the invention

[0004] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a sodium ion battery layered oxide positive electrode material and a preparation method thereof, which solves the problem that the existing sodium ion battery layered oxide positive electrode material is prone to phase change and cracking during the cycle process, resulting in a significant decrease in battery performance.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a sodium ion battery layered oxide positive electrode material comprises the following steps:

[0007] Step 1: Add cyanuric chloride, 2-bromo-4-trifluoromethylphenol, anhydrous potassium carbonate, acetone and toluene into a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then heat to 120-130° C. and continue to stir and react for 8-10 hours. After the reaction is completed, cool the reaction product to room temperature, then add it to ice water, and then vacuum filter it, wash the filter cake with anhydrous ethanol 2-3 times, and then place it in a vacuum drying oven, and dry it at a temperature of 70-75° C. for 3-5 hours to obtain an intermediate product 1;

[0008] Step 2: Add the intermediate product 1, carbazole, anhydrous potassium carbonate and N, N-dimethylformamide to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then add cuprous iodide and 1,10-phenanthroline and continue stirring and reacting for 20-30 hours under the condition of heating to 140-150° C., and after the reaction is completed, cool the reaction product to room temperature, then add it to ice water, then vacuum filter, add the filter cake to dichloromethane, then wash it with distilled water 2-3 times, then dry it with anhydrous magnesium sulfate, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain the intermediate product 2;

[0009] Step 3: Add the composite layered oxide, anhydrous ferric chloride and chloroform to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 20-25°C and a stirring rate of 300-400r / min, then add the chloroform solution of the intermediate product 2 dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to 40-50°C and the stirring reaction is continued for 20-30 hours. After the reaction is completed, the reaction product is cooled to room temperature, then added to anhydrous methanol, and then vacuum filtered. The filter cake is washed with hydrochloric acid solution and distilled water for 3-5 times in turn, and then placed in a vacuum drying oven and dried at a temperature of 80-85°C for 4-6 hours to obtain a sodium ion battery layered oxide positive electrode material.

[0010] As a further scheme of the present invention: the usage ratio of the cyanuric chloride, 2-bromo-4-trifluoromethylphenol, anhydrous potassium carbonate, acetone and toluene in step 1 is 10mmol:30mmol:35-40mmol:40-50mL:15-25mL.

[0011] As a further scheme of the present invention: the usage ratio of the intermediate product 1 in step 2, carbazole, anhydrous potassium carbonate, N,N-dimethylformamide, cuprous iodide and 1,10-phenanthroline is 10mmol:35-45mmol:50-55mmol:60-80mL:1.8-2.4g:0.33-0.39g.

[0012] As a further solution of the present invention: the usage ratio of the composite layered oxide, anhydrous ferric chloride, chloroform and the chloroform solution of the intermediate product 2 in step 3 is 1g: 0.5-0.6g: 20-25mL: 10-12mL.

[0013] As a further solution of the present invention: the chloroform solution of the intermediate product 2 in step 3 is a solution formed by dissolving the intermediate product 2 in chloroform at a ratio of 0.2-0.3 g:10 mL.

[0014] As a further solution of the present invention: the mass fraction of the hydrochloric acid solution in step three is 10-12%.

[0015] As a further solution of the present invention: the general chemical formula of the composite layered oxide in step 3 is: Na w Ni x Fe y Mn 1-x-y M z O 2 ;

[0016] Wherein, M is Ti, Cr, Al, Co, Mg, Zn, Zr, Nb, Cu;

[0017] Among them, w, x, y and z satisfy 0.5≤w≤2, 0≤x≤1, 0≤y≤1, 0≤z≤0.1.

[0018] As a further solution of the present invention: the composite layered oxide is in granular form with a particle size of 5-15 μm.

[0019] As a further solution of the present invention: the composite layered oxide is prepared by the following steps:

[0020] Step A1: adding sodium salt, precursor and metal oxide into a high speed mixer, stirring and mixing for 0.5-2h at a stirring rate of 800-1000r / min, and putting into a sagger for cutting into blocks of 3cm×3cm×5cm with a cutting gap of 5mm to obtain a mixed material block;

[0021] Step A2: Place the mixed material block in a box furnace, heat it to 700-1000°C at a heating rate of 5-10°C / min in an air atmosphere, then calcine it for 10-15h, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a composite layered oxide.

[0022] As a further solution of the present invention: the sodium salt in step A1 is at least one of sodium carbonate and sodium acetate.

[0023] As a further solution of the present invention: the precursor in step A1 is a mixture of nickel sulfate, ferrous sulfate and manganese sulfate.

[0024] As a further embodiment of the present invention: the metal oxide in step A1 is TiO 2 Cr 2 O3 、Al 2 O 3 、CoO、ZnO、ZrO 2 , Nb 2 O 5 and at least one of CuO.

[0025] As a further solution of the present invention: the composite layered oxide is prepared by the following steps:

[0026] Step S1: According to the molar ratio of w:x:y:1-xy:z=1:0.3:0.3:0.4:0.05, accurately weigh the corresponding masses of sodium carbonate, nickel sulfate, ferrous sulfate, manganese sulfate and Mg(OH) 2 Add to high-speed mixer, stir and mix for 1 hour at a stirring rate of 1000 r / min, put into sagger and cut into 3cm×3cm×5cm blocks with a cutting gap of 5mm to obtain mixed material blocks;

[0027] Step S2: Place the mixed material block in a box furnace, heat it to 870°C at a heating rate of 10°C / min in an air atmosphere, then calcine it for 12 hours, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a composite layered oxide.

[0028] As a further solution of the present invention: a sodium ion battery layered oxide positive electrode material, wherein the sodium ion battery layered oxide positive electrode material is prepared according to the preparation method of the sodium ion battery layered oxide positive electrode material.

[0029] Beneficial effects of the present invention:

[0030] The sodium ion battery layered oxide positive electrode material and the preparation method thereof are as follows: sodium salt, a precursor and a metal oxide are added into a high-speed mixer and mixed evenly, then cut into pieces and calcined to obtain a composite layered oxide; then cyanuric chloride and 2-bromo-4-trifluoromethylphenol are reacted, chlorine atoms on the cyanuric chloride react with hydroxyl groups on the 2-bromo-4-trifluoromethylphenol to form a large number of benzene rings, bromine atoms and a hyperbranched skeleton of trifluoromethyl to obtain an intermediate product one; then the intermediate product one and carbazole are reacted, bromine atoms on the intermediate product one react with secondary amine groups on the carbazole to introduce a large number of carbazole rings to obtain an intermediate product two; finally, the intermediate product two is used as a polymerization monomer to polymerize on the surface of the composite layered oxide to form polycarbazole to coat the composite layered oxide to obtain the sodium ion battery layered oxide positive electrode material;

[0031] The composite layered oxide of the present invention is composed of two or more metal ions and has excellent electrochemical properties. At high temperature, the precursor substances diffuse with each other, so that the microscopic discrete particles gradually form a continuous solid layered structure, thereby obtaining a stable sodium-containing triclinic layered oxide material, so that the material has a smaller volume change in the electrochemical process, giving the positive electrode material an ultra-long cycle stability life, thereby improving the battery performance. The polycarbazole wrapped on the composite layered oxide is then directly polymerized with carbazole to form polycarbazole. After the benzene ring is introduced and the number of carbazole rings is increased, the polycarbazole has a higher contact area and a π-conjugated structure, which has a great impact on the composite. The layered oxide has a higher degree of wrapping and greatly improved conductivity. The polycarbazole used for wrapping can serve as a protective layer, which can not only effectively isolate the direct contact between the composite layered oxide and the electrolyte, reduce the structural destruction of the composite layered oxide and the dissolution of active substances caused by electrolyte corrosion, but also inhibit the volume change caused by the uneven embedding and extraction of sodium ions during the charge and discharge process, thereby significantly improving the cycle stability of the material. In addition, the fluorine atoms in the polycarbazole protective layer can give it excellent high-temperature stability and chemical stability, making the protection effect better and further improving the cycle stability of the positive electrode material. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1a:

[0034] This embodiment is a method for preparing a layered oxide positive electrode material for a sodium ion battery, comprising the following steps:

[0035] Step S1: According to the molar ratio of w:x:y:1-xy:z=1:0.3:0.3:0.4:0.05, accurately weigh the corresponding masses of sodium carbonate, nickel sulfate, ferrous sulfate, manganese sulfate and Al 2 O 3 Add to high-speed mixer, stir and mix for 1 hour at a stirring rate of 1000 r / min, put into sagger and cut into 3cm×3cm×5cm blocks with a cutting gap of 5mm to obtain mixed material blocks;

[0036] Step S2: Place the mixed material block in a box furnace, heat it to 870°C at a heating rate of 10°C / min in an air atmosphere, and then calcine it for 12 hours, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a sodium ion battery layered oxide positive electrode material with a molecular formula of NaNi 0.3 Fe 0.3 Mn 0.4 Al 0.05 O 2 .

[0037] Embodiment 1b:

[0038] This embodiment is a method for preparing a layered oxide positive electrode material for a sodium ion battery, comprising the following steps:

[0039] Step S1: According to the molar ratio of w:x:y:1-xy:z=1:0.3:0.3:0.4:0.05, accurately weigh the corresponding masses of sodium carbonate, nickel sulfate, ferrous sulfate, manganese sulfate and Al 2 O 3 Add to high-speed mixer, stir and mix for 1 hour at a stirring rate of 1000 r / min, put into sagger and cut into 3cm×3cm×5cm blocks with a cutting gap of 5mm to obtain mixed material blocks;

[0040] Step S2: Place the mixed material block in a box furnace, heat it to 870°C at a heating rate of 10°C / min in an air atmosphere, and then calcine it for 12 hours, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a composite layered oxide with a molecular formula of NaNi 0.3 Fe 0.3 Mn 0.4 Al 0.05 O 2 ;

[0041] Step S3: 10mmol cyanuric chloride, 30mmol 2-bromo-4-trifluoromethylphenol, 40mmol anhydrous potassium carbonate, 50mL acetone and 25mL toluene are added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30°C and a stirring rate of 400r / min for 30min, and then the mixture is heated to 130°C and stirred for reaction for 10h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake is washed with anhydrous ethanol for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 75°C for 5h to obtain an intermediate product 1.

[0042] Step S4: 10 mmol of the intermediate product 1, 45 mmol of carbazole, 55 mmol of anhydrous potassium carbonate and 80 mL of N, N-dimethylformamide are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then 2.4 g of cuprous iodide and 0.39 g of 1,10-phenanthroline are added and the temperature is raised to 150° C. and the stirring reaction is continued for 30 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake is added to dichloromethane, and then washed with distilled water for 3 times, and then dried with anhydrous magnesium sulfate, and then vacuum filtered. The filtrate is rotary evaporated to remove the solvent to obtain the intermediate product 2;

[0043] Step S5: 1g of composite layered oxide, 0.6g of anhydrous ferric chloride and 25mL of chloroform are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The reaction is stirred for 30 minutes at a temperature of 25°C and a stirring rate of 400r / min. Then, 12mL of the intermediate product 2 is dissolved in chloroform at a ratio of 0.3g:10mL to form a chloroform solution of the intermediate product 2, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the temperature is raised to 50°C and the stirring reaction is continued for 30 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then added to anhydrous methanol, and then vacuum filtered. The filter cake is washed 5 times with a mass fraction of 12% hydrochloric acid solution and distilled water in turn, and then placed in a vacuum drying oven and dried at a temperature of 85°C for 6 hours to obtain a sodium ion battery layered oxide positive electrode material.

[0044] Example 2a:

[0045] This embodiment is a method for preparing a layered oxide positive electrode material for a sodium ion battery, comprising the following steps:

[0046] Step S1: According to the molar ratio of w:x:y:1-xy:z=1:0.3:0.3:0.4:0.05, accurately weigh the corresponding masses of sodium carbonate, nickel sulfate, ferrous sulfate, manganese sulfate and Mg(OH) 2 Add to high-speed mixer, stir and mix for 1 hour at a stirring rate of 1000 r / min, put into sagger and cut into 3cm×3cm×5cm blocks with a cutting gap of 5mm to obtain mixed material blocks;

[0047] Step S2: Place the mixed material block in a box furnace, heat it to 870°C at a heating rate of 10°C / min in an air atmosphere, and then calcine it for 12 hours, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a sodium ion battery layered oxide positive electrode material with a molecular formula of NaNi 0.3 Fe 0.3 Mn 0.4 Mg 0.05 O 2 .

[0048] Example 2b:

[0049] This embodiment is a method for preparing a layered oxide positive electrode material for a sodium ion battery, comprising the following steps:

[0050] Step S1: According to the molar ratio of w:x:y:1-xy:z=1:0.3:0.3:0.4:0.05, accurately weigh the corresponding masses of sodium carbonate, nickel sulfate, ferrous sulfate, manganese sulfate and Mg(OH) 2 Add to high-speed mixer, stir and mix for 1 hour at a stirring rate of 1000 r / min, put into sagger and cut into 3cm×3cm×5cm blocks with a cutting gap of 5mm to obtain mixed material blocks;

[0051] Step S2: Place the mixed material block in a box furnace, heat it to 870°C at a heating rate of 10°C / min in an air atmosphere, and then calcine it for 12 hours, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a composite layered oxide with a molecular formula of NaNi 0.3 Fe 0.3 Mn 0.4 Mg 0.05 O 2 ;

[0052] Step S3: 10mmol cyanuric chloride, 30mmol 2-bromo-4-trifluoromethylphenol, 40mmol anhydrous potassium carbonate, 50mL acetone and 25mL toluene are added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30°C and a stirring rate of 400r / min for 30min, and then the mixture is heated to 130°C and stirred for reaction for 10h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake is washed with anhydrous ethanol for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 75°C for 5h to obtain an intermediate product 1.

[0053] Step S4: 10 mmol of the intermediate product 1, 45 mmol of carbazole, 55 mmol of anhydrous potassium carbonate and 80 mL of N, N-dimethylformamide are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then 2.4 g of cuprous iodide and 0.39 g of 1,10-phenanthroline are added and the temperature is raised to 150° C. and the stirring reaction is continued for 30 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake is added to dichloromethane, and then washed with distilled water for 3 times, and then dried with anhydrous magnesium sulfate, and then vacuum filtered. The filtrate is rotary evaporated to remove the solvent to obtain the intermediate product 2;

[0054] Step S5: 1g of composite layered oxide, 0.6g of anhydrous ferric chloride and 25mL of chloroform are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The reaction is stirred for 30 minutes at a temperature of 25°C and a stirring rate of 400r / min. Then, 12mL of the intermediate product 2 is dissolved in chloroform at a ratio of 0.3g:10mL to form a chloroform solution of the intermediate product 2, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the temperature is raised to 50°C and the stirring reaction is continued for 30 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then added to anhydrous methanol, and then vacuum filtered. The filter cake is washed 5 times with a mass fraction of 12% hydrochloric acid solution and distilled water in turn, and then placed in a vacuum drying oven and dried at a temperature of 85°C for 6 hours to obtain a sodium ion battery layered oxide positive electrode material.

[0055] Example 3a:

[0056] This embodiment is a method for preparing a layered oxide positive electrode material for a sodium ion battery, comprising the following steps:

[0057] Step S1: According to the molar ratio of w:x:y:1-xy:z=1:0.3:0.4:0.3:0.02, accurately weigh the corresponding mass of sodium carbonate, nickel sulfate, ferrous sulfate, manganese sulfate and Nb 2 O 5 Add to high-speed mixer, stir and mix for 1 hour at a stirring rate of 1000 r / min, put into sagger and cut into 3cm×3cm×5cm blocks with a cutting gap of 5mm to obtain mixed material blocks;

[0058] Step S2: Place the mixed material block in a box furnace, heat it to 870°C at a heating rate of 10°C / min in an air atmosphere, and then calcine it for 12 hours, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a sodium ion battery layered oxide positive electrode material with a molecular formula of NaNi 0.3 Fe 0.4 Mn 0.3 Nb 0.02 O 2 .

[0059] Example 3b:

[0060] This embodiment is a method for preparing a layered oxide positive electrode material for a sodium ion battery, comprising the following steps:

[0061] Step S1: According to the molar ratio of w:x:y:1-xy:z=1:0.3:0.4:0.3:0.02, accurately weigh the corresponding mass of sodium carbonate, nickel sulfate, ferrous sulfate, manganese sulfate and Nb 2 O 5 Add to high-speed mixer, stir and mix for 1 hour at a stirring rate of 1000 r / min, put into sagger and cut into 3cm×3cm×5cm blocks with a cutting gap of 5mm to obtain mixed material blocks;

[0062] Step S2: Place the mixed material block in a box furnace, heat it to 870°C at a heating rate of 10°C / min in an air atmosphere, and then calcine it for 12 hours, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a composite layered oxide with a molecular formula of NaNi 0.3 Fe 0.4 Mn 0.3 Nb 0.02 O 2 ;

[0063] Step S3: 10mmol cyanuric chloride, 30mmol 2-bromo-4-trifluoromethylphenol, 40mmol anhydrous potassium carbonate, 50mL acetone and 25mL toluene are added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30°C and a stirring rate of 400r / min for 30min, and then the mixture is heated to 130°C and stirred for reaction for 10h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake is washed with anhydrous ethanol for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 75°C for 5h to obtain an intermediate product 1.

[0064] Step S4: 10 mmol of the intermediate product 1, 45 mmol of carbazole, 55 mmol of anhydrous potassium carbonate and 80 mL of N, N-dimethylformamide are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then 2.4 g of cuprous iodide and 0.39 g of 1,10-phenanthroline are added and the temperature is raised to 150° C. and the stirring reaction is continued for 30 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake is added to dichloromethane, and then washed with distilled water for 3 times, and then dried with anhydrous magnesium sulfate, and then vacuum filtered. The filtrate is rotary evaporated to remove the solvent to obtain the intermediate product 2;

[0065] Step S5: 1g of composite layered oxide, 0.6g of anhydrous ferric chloride and 25mL of chloroform are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The reaction is stirred for 30 minutes at a temperature of 25°C and a stirring rate of 400r / min. Then, 12mL of the intermediate product 2 is dissolved in chloroform at a ratio of 0.3g:10mL to form a chloroform solution of the intermediate product 2, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the temperature is raised to 50°C and the stirring reaction is continued for 30 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then added to anhydrous methanol, and then vacuum filtered. The filter cake is washed 5 times with a mass fraction of 12% hydrochloric acid solution and distilled water in turn, and then placed in a vacuum drying oven and dried at a temperature of 85°C for 6 hours to obtain a sodium ion battery layered oxide positive electrode material.

[0066] Embodiment 4a:

[0067] This embodiment is a method for preparing a layered oxide positive electrode material for a sodium ion battery, comprising the following steps:

[0068] Step S1: according to the molar ratio of w:x:y:1-xy:z=1:0.3:0.3:0.4:0.05, accurately weigh corresponding masses of sodium carbonate, nickel sulfate, ferrous sulfate, manganese sulfate and CoO, add them into a high-speed mixer, stir and mix them at a stirring rate of 1000r / min for 1h, put them into a sagger after mixing evenly, cut them into 3cm×3cm×5cm pieces with a cutting gap of 5mm, and obtain a mixed material block;

[0069] Step S2: Place the mixed material block in a box furnace, heat it to 870°C at a heating rate of 10°C / min in an air atmosphere, and then calcine it for 12 hours, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a sodium ion battery layered oxide positive electrode material with a molecular formula of NaNi 0.3 Fe 0.3 Mn 0.4 Co 0.05 O 2 .

[0070] Embodiment 4b:

[0071] This embodiment is a method for preparing a layered oxide positive electrode material for a sodium ion battery, comprising the following steps:

[0072] Step S1: according to the molar ratio of w:x:y:1-xy:z=1:0.3:0.3:0.4:0.05, accurately weigh corresponding masses of sodium carbonate, nickel sulfate, ferrous sulfate, manganese sulfate and CoO, add them into a high-speed mixer, stir and mix them at a stirring rate of 1000r / min for 1h, put them into a sagger after mixing evenly, cut them into 3cm×3cm×5cm pieces with a cutting gap of 5mm, and obtain a mixed material block;

[0073] Step S2: Place the mixed material block in a box furnace, heat it to 870°C at a heating rate of 10°C / min in an air atmosphere, and then calcine it for 12 hours, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a composite layered oxide with a molecular formula of NaNi 0.3 Fe 0.3 Mn 0.4 Co 0.05 O 2 ;

[0074] Step S3: 10mmol cyanuric chloride, 30mmol 2-bromo-4-trifluoromethylphenol, 40mmol anhydrous potassium carbonate, 50mL acetone and 25mL toluene are added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30°C and a stirring rate of 400r / min for 30min, and then the mixture is heated to 130°C and stirred for reaction for 10h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake is washed with anhydrous ethanol for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 75°C for 5h to obtain an intermediate product 1.

[0075] Step S4: 10 mmol of the intermediate product 1, 45 mmol of carbazole, 55 mmol of anhydrous potassium carbonate and 80 mL of N, N-dimethylformamide are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then 2.4 g of cuprous iodide and 0.39 g of 1,10-phenanthroline are added and the temperature is raised to 150° C. and the stirring reaction is continued for 30 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then vacuum filtered. The filter cake is added to dichloromethane, and then washed with distilled water for 3 times, and then dried with anhydrous magnesium sulfate, and then vacuum filtered. The filtrate is rotary evaporated to remove the solvent to obtain the intermediate product 2;

[0076] Step S5: 1g of composite layered oxide, 0.6g of anhydrous ferric chloride and 25mL of chloroform are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The reaction is stirred for 30 minutes at a temperature of 25°C and a stirring rate of 400r / min. Then, 12mL of the intermediate product 2 is dissolved in chloroform at a ratio of 0.3g:10mL to form a chloroform solution of the intermediate product 2, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the temperature is raised to 50°C and the stirring reaction is continued for 30 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then added to anhydrous methanol, and then vacuum filtered. The filter cake is washed 5 times with a mass fraction of 12% hydrochloric acid solution and distilled water in turn, and then placed in a vacuum drying oven and dried at a temperature of 85°C for 6 hours to obtain a sodium ion battery layered oxide positive electrode material.

[0077] Performance Testing:

[0078] The sodium ion battery layered oxide positive electrode material of Examples 1a-4a and Examples 1b-4b, Super P conductive carbon black and polyvinylidene fluoride were mixed uniformly in a mass ratio of 8:1:1, and then N-methyl-2-pyrrolidone was added and mixed uniformly to form a positive electrode slurry. The positive electrode slurry was then coated on the surface of aluminum foil and dried completely as a positive electrode sheet. A sodium metal sheet was used as a negative electrode, a glass fiber mesh was used as a separator, and a concentration of 1 mol / L NaClO 4 / (EC+DMC with a volume ratio of 1:1) was used as the electrolyte to assemble button cells in a glove box filled with high-purity argon. The button cells made of each group of positive electrode materials were subjected to electrochemical tests. The test conditions were 25°C, the voltage range was 2.0-4.0V, and the rate was 0.1C. The test results are shown in the following table:

[0079]

[0080] Referring to the data in the above table, according to the comparison between Examples 1a-4a and Examples 1b-4b, it can be seen that the positive electrode sheet prepared by directly using the composite layered oxide as the positive electrode material has excellent electrochemical properties, but its cycle stability is not good, and the electrochemical performance of the positive electrode sheet prepared by using the composite layered oxide coated with a conductive polymer as the positive electrode material is slightly improved, but its cycle stability is greatly improved, thereby improving the overall performance of the sodium ion battery.

[0081] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0082] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a layered oxide positive electrode material for a sodium ion battery, characterized in that: The following steps are involved: Step 1: stirring cyanuric chloride, 2-bromo-4-trifluoromethylphenol, anhydrous potassium carbonate, acetone and toluene for reaction, cooling the reaction product after the reaction, then adding it into ice water, then vacuum filtering, washing and drying the filter cake to obtain an intermediate product 1; the amount ratio of cyanuric chloride, 2-bromo-4-trifluoromethylphenol, anhydrous potassium carbonate, acetone and toluene in step 1 is 10mmol:30mmol:35-40mmol:40-50mL:15-25mL; Step 2: Stir and react the intermediate product 1, carbazole, anhydrous potassium carbonate and N, N-dimethylformamide, then add cuprous iodide and 1,10-phenanthroline and continue stirring and reacting, and after the reaction, cool the reaction product, then add it into ice water, then vacuum filter, add the filter cake into dichloromethane, then wash and dry, then vacuum filter, and rotary evaporate the filtrate to obtain the intermediate product 2; the amount ratio of the intermediate product 1, carbazole, anhydrous potassium carbonate, N, N-dimethylformamide, cuprous iodide and 1,10-phenanthroline in step 2 is 10mmol:35-45mmol:50-55mmol:60-80mL:1.8-2.4g:0.33-0.39g; Step 3: Stir the composite layered oxide, anhydrous ferric chloride and chloroform for reaction, then add the chloroform solution of the intermediate product 2 dropwise while stirring, continue stirring for reaction after the dropwise addition is completed, cool the reaction product after the reaction is completed, then add it to anhydrous methanol, then vacuum filter, wash and dry the filter cake to obtain a sodium ion battery layered oxide positive electrode material; the amount ratio of the composite layered oxide, anhydrous ferric chloride, chloroform and the chloroform solution of the intermediate product 2 in step 3 is 1g: 0.5-0.6g: 20-25mL: 10-12mL; the chloroform solution of the intermediate product 2 is a solution formed by dissolving the intermediate product 2 in chloroform according to 0.2-0.3g: 10mL; The general chemical formula of the composite layered oxide is: Na w Ni x Fe y Mn 1-x-y M z O2; Wherein, M is Ti, Cr, Al, Co, Mg, Zn, Zr, Nb, Cu; Among them, w, x, y and z satisfy 0.5≤w≤2, 0≤x≤1, 0≤y≤1, 0≤z≤0.

1.

2. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: The composite layered oxide is in granular form with a particle size of 5-15 μm.

3. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: The composite layered oxide is prepared by the following steps: Step A1: adding sodium salt, precursor and metal oxide into a high speed mixer, stirring and mixing for 0.5-2h at a stirring rate of 800-1000r / min, and putting into a sagger for cutting into blocks of 3cm×3cm×5cm with a cutting gap of 5mm to obtain a mixed material block; Step A2: Place the mixed material block in a box furnace, heat it to 700-1000°C at a heating rate of 5-10°C / min in an air atmosphere, then calcine it for 10-15h, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a composite layered oxide.

4. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 3, characterized in that: The sodium salt in step A1 is at least one of sodium carbonate and sodium acetate; the precursor is a mixture of nickel sulfate, ferrous sulfate and manganese sulfate; the metal oxide is at least one of TiO2, Cr2O3, Al2O3, CoO, ZnO, ZrO2, Nb2O5 and CuO.

5. The method for preparing the layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: The composite layered oxide is prepared by the following steps: Step S1: according to the molar ratio of w:x:y:1-xy:z=1:0.3:0.3:0.4:0.05, accurately weigh corresponding masses of sodium carbonate, nickel sulfate, ferrous sulfate, manganese sulfate and Mg(OH)2 and add them into a high-speed mixer, stir and mix them at a stirring rate of 1000r / min for 1h, and after mixing evenly, put them into a sagger for cutting into 3cm×3cm×5cm blocks with a cutting gap of 5mm to obtain a mixed material block; Step S2: Place the mixed material block in a box furnace, heat it to 870°C at a heating rate of 10°C / min in an air atmosphere, then calcine it for 12 hours, then cool it to room temperature with the furnace, and then crush it through a 300-mesh sieve to obtain a composite layered oxide.

6. A layered oxide positive electrode material for a sodium ion battery, characterized in that: The sodium ion battery layered oxide positive electrode material is prepared according to the method for preparing a sodium ion battery layered oxide positive electrode material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Organic electroluminescent element

    CN102696126A

  • Surface-coated Positive Electrode Active Material Particles And Secondary Battery Comprising The Same

    US20200127284A1